A Chronicle of the Soviet Tuva (1950s-1960s) in the Diaries of Salchak Toka - Grygory Ch. Shirshin (Novye Issledovaniâ Tuvy, 2017)
The article examines the diaries of Salchak Kalakbakhorekhovich Toka (1901-1973), a prominent statesman and public figure of the Republic of Tuva, First Secretary of the Central Committee of Tuva People’s Revolutionary Party (1932-1944), First Secretary of Tuva Oblast Committee of the CPSU (1944-1973). Toka’s work as a party official has been covered in detail by historians, both in the Soviet and post-Soviet periods. In 2012, his 110th anniversary was celebrated in the region, and a dedicated research conference was held to honor him.